2016
DOI: 10.1186/s13071-016-1809-6
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasite infections and associated risk factors in communities exposed to wastewater in urban and peri-urban transition zones in Hanoi, Vietnam

Abstract: BackgroundInfections with intestinal parasites (helminths and intestinal protozoa) are endemic in Southeast Asia and inappropriate management and reuse of wastewater might exacerbate the risk of human infections. In rapidly growing urban settings, little is known about the extent of intestinal parasite infections. We assessed the point-prevalence and risk factors of intestinal parasite infections in population groups differently exposed to wastewater in urban and peri-urban transition zones in Hanoi, the capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Public health interventions which focus on the provision of basic sanitation infrastructure, health education, and target drug administration are essential to prevent and control these parasitic diseases [5]. These measures should be based and adapted to a local context to assure their success and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Public health interventions which focus on the provision of basic sanitation infrastructure, health education, and target drug administration are essential to prevent and control these parasitic diseases [5]. These measures should be based and adapted to a local context to assure their success and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Results of a Kampala study revealed that sewer-men presented with lower detection rates than farmers who used untreated waste water to grow their crops (76%) [48] . Also, a study conducted by Fuhrimann et al [50] in different communities exposed to waste water in urban and peri-urban transition zones in Hanoi, Vietnam, showed that waste water exposure was not directly associated with IPIs. The investigators explained their conclusion by the high level of awareness of the population to the different health risks [50] .…”
Section: Discussionmentioning
confidence: 97%
“…1 The disease control was achieved by implementation of both the national control system and improvement of environment and sanitation. 6 Occasionally, sporadic cases occur in non-endemic, developed areas, because of immigration. 2 Therefore, to date, coming across a patient with parasite infection of T. trichiura in South Korea is highly rare in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Such knowledge leads us to presume a high prevalence of intestinal parasitic infection in North Korea. 6 Recently, a single tertiary hospital in South Korea reported clinical characteristics of defectors from North Korea. In children, heavy colonic infection called TDS causes diarrhea with blood or mucus, rectal prolapse, and iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%